(3eHGMK aj GdCUhds - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3GdCeQ GdJGSY aj KHhJ GdMbjbI GdTQYjI hYOeg hbO GNJdahG ajgG Ydi CbhGd GdKHhJ eWdbGJ hGdYOe eWdkbG hGdJaUjd aj GdCdaGXs
(3BNQgG (B:s
(3BNQgG(B: (3Hd gj Ydi eG gj Ydjg fYe HGdfSHI Edi Yde GdBeQ dg ONd ajgG hcPdc HGdfSHI Edi ebGe GdGeJKGds
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3CUhd Gdabgs